Impact of chronic coronary syndromes on cardiovascular hospitalization and mortality: the ESC-EORP CICD-LT registry. (14th October 2021) - Kerneis, M; Cosentino, F; Ferrari, R; Georges, J L; Kosmachova, E; Laroche, C; Maggioni, A P; Rittger, H; Steg, P G; Szwed, H; Tavazzi, L; Valgimigli, M; et al.
Abstract: Background: In Europe, global data on guideline adherence, potential geographic variations and determinants of major clinical events in chronic coronary syndromes (CCS) remain suboptimal. The European Society of Cardiology (ESC) EURObservational Research Programme (EORP) Chronic Ischemic Cardiovascular Disease Long-Term (CICD-LT) registry, a prospective European registry, was designed and conducted to describe the profile, care and outcomes of patients with CCS across the ESC countries Purpose: We aimed to investigate clinical events at one-year follow-up from the ESC EORP CICD-LT Registry and identify the variables associated with an increased risk of clinical events. Methods: Consecutive adults presenting with a diagnosis of CCS during a routine ambulatory visit or an elective coronary revascularisation procedure at participating centres were recruited across 154 centers from 20 countries between 1 May 2015 and 31 July 2018. Information on clinical and survival status was collected after 1 year from study inclusion. Composite events were cardio-vascular (CV) mortality and/or CV rehospitalisations, all-cause mortality and/or all cause rehospitalisation. A multivariable Cox regression analysis was performed to identify the independent predictors of each composite. Cox models were also performed with age, sex and region forced in the model. Significance levels of 0.05 were required to allow a variable to stay within the model. Co-linearity between all candidate variables (variables with p<0.05 in univariable) within the model and variables considered of relevant clinical interest were tested before proceeding to the multivariable model. Missing data were not imputed. Results: One-year outcomes of 6655 patients from the 9174 recruited in this European registry were analyzed. Overall, 168 patients (2.5%) died, mostly from CV causes (n=97, 1.5%). Northern Europe had the lowest CV mortality rate, while southern Europe had the highest (0.5% vs 2.0%, p=0.04). Women had a higher rate of CV mortality compared with men (2.0% vs 1.3%, p=0.02). During follow-up, 1606 patients (27.1%) were hospitalised at least once, predominantly for CV indications (n=1220, 20.6%). Among the population with measured LDL-cholesterol level at one year, 1434 patients (66.5%) were above the currently recommended target. Age, history of atrial fibrillation, previous stroke, liver disease, chronic obstructive pulmonary disease or asthma, increased serum creatinine and impaired left ventricular function were each independently associated with an increased risk of CV death or hospitalization. Conclusion: In the CICD registry, the majority of patients with CCS have uncontrolled CV risk factors. The mortality rate at one year was low, but these patients are frequently hospitalised for CV causes. Early identification of comorbidities may represent an opportunity for enhanced care and better outcomes. FUNDunding Acknowledgement: Type of funding sources: Other. Main funding source(s): The study was funded by the EORP program.